Proses Efisiensi Container Direct pada PT. Salam Pacific Indonesia Lines Cabang Medan - Arfansyah Tanjung; Nurmaliana Sari Siregar (Jurnal Bisnis Inovatif dan Digital, 2025)
PT Salam Pacific Indonesia Lines Medan branch is a large-scale domestic shipping company that provides logistics and sea transportation services, particularly inter-island container shipping throughout Indonesia. This paper discusses how efficiency is applied to direct container activities at the Medan branch. The work stages begin with the accurate identification of tentative cargo. Direct officers first obtain data on the number of containers from the depot head, including the prefix, condition (grade), and size of the containers to be processed. After that, officers check the completeness of documents and conduct physical checks in accordance with company operational regulations. If all requirements are met, containers are directed for direct shipping based on Customer requests and the tentative ship loading schedule that has been set. Next, officers issue an SP2 or Container Delivery Letter as a requirement for entering the port gate. With this flow, the process can support the efficiency of the container cycle in the empty container handling system. However, obstacles are still found, such as complex administrative processes, missing documents, and information that has not been communicated properly. Therefore, intensive coordination with the authorities is needed so that direct activities run smoothly. This paper uses field observation and literature study methods to obtain relevant data.